Novel Metamaterial Structures with Low Loss at Millimeter Wave Frequency Range - B. A. F. Esmail; H. A. Majid; S. H. Dahlan; Z. Z. Abidin; M. K. A. Rahim; R. Dewan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Two novel millimeter-wave (MMW) metamaterials (MTMs) unit cells operate at 28 GHz for a future fifth generation (5G) mobile network applications had been designed, presented and numerically investigated. Two MTM structures are proposed; namely the double E-shaped resonator (DER) and T-U shaped resonator (TUSR). The DER and TUSR are consists of a double E and combined T-U shaped, each printed on front side of the substrate layer respectively. DER achieves a bandwidth of 0.5 GHz and a return loss of -34 dB, whereas TUSR features a bandwidth of  0.3 GHz and a return loss of -18 dB. The conventional split range resonator (SRR) was optimized to operate at similar frequency for comparison purpose. The simulation results revealed that the proposed DER and TUSR unit cells achieves the lowest loss as opposed to literature with -0.09 dB (0.99 in linear scale) and -0.23 dB (0.97 in linear scale) respectively. Moreover, a well-known algorithm was used to extract the constitutive parameters and the double negative nature of the two novel MTM structures is proven.